A Lagoa do Banana, Caucaia/Ce e os impactos socioambientais do veraneio e turismo - Farrapo, Sâmila de Paulo (2013)
This study aims to analyze the social and environmental impacts in Banana Lake, located in Caucaia, metropolitan region of Ceará. The study addresses the intensifying human activities in the region for leisure and tourism activities in the lagoon and its surroundings, which is used by swimmers and water sports. The study can be divided into two phases. The first refers to the bibliographic and documentary and the second stage deals with the experimental investigation. The socio-environmental study was done methodologically in a qualitative and exploratory, seeking to detect the impacts of tourism activities and growth in the real estate market around the pond. There was water quality, using as a methodology the Water Quality Index (AQI), where there were two campaigns (May and November/2012), during periods of rain and drought, analyzing the parameters of temperature, pH, turbidity dissolved oxygen (DO), biochemical oxygen demand (BOD), total nitrogen, total phosphorus, total solids and fecal coliform. The results showed that the concentration of total phosphorus is allowed to exceed the level at all points during the dry period, and off limits to be allowed by CONAMA Resolution No. 357/2005 establishing the maximum permissible concentration is to 0.03 mg / L for class I to this parameter. The other variables are in line with current legislation in both campaigns. The water, according to CONAMA Resolution No. 274/2000, has category "Very Good", during the rainy and "satisfactory" period during the dry period. However, the mass of activities in the region has promoted the loss of riparian forest, alteration of the natural landscape and change in quality of life of the local population. There is no supervision of the activities carried out within the pond and buildings are being built in areas that should be permanent preservation areas. Makes if necessary to adopt mitigating measures with the intention of promoting sustainable development.